Bureaucratic Performance in the Service of Natural Disaster Victims at the Langkat Regency Social Office - Suriadi Nina; Nina Siti Salmaniah Siregar; Budi Hartono (Journal of Social Interactions and Humanities, 2024)
The purpose of this study is to describe the performance of the bureaucracy and the factors that influence it in the service of victims of natural disasters at the Langkat Regency Social Office. This study used qualitative descriptive research method. Data collection techniques use observation, interviews and documentation studies. Data analysis is carried out by reducing data, presenting data, and drawing conclusions. Based on the results of data analysis, it can be concluded that the Social Office of Langkat Regency has unsatisfactory services. The system that runs so far will be more efficient and better if continuous improvements are made. The services of the Social Service of Langkat Regency are mostly constrained by time. Knowledge of employees, providing direction, and also decision making is not able to be carried out properly. There are still weaknesses in the ability of the Social Office of Langkat Regency to serve the community such as the difficulty of being contacted, found and asked for services is a point that must be improved by the Social Office of Langkat District. To improve and improve bureaucratic performance in services for victims of natural disasters at the Langkat Regency Social Office, researchers suggest that services can be evaluated on an ongoing basis, related to communication services that become a driver for the community can be improved in each service unit, so that the community does not need to spend time to carry out a long process in managing the services needed.